Development of a robot‐assisted kidney transplantation programme from deceased donors in a referral academic centre: technical nuances and preliminary results. (6th November 2018) - Vignolini, Graziano; Campi, Riccardo; Sessa, Francesco; Greco, Isabella; Larti, Aida; Giancane, Saverio; Sebastianelli, Arcangelo; Gacci, Mauro; Peris, Adriano; Li Marzi, Vincenzo; Breda, Alberto; Siena, Giampaolo; et al.
Abstract : Objective: To report the development of the first robot‐assisted kidney transplantation (RAKT) programme from deceased donors, examining technical feasibility and early perioperative and functional outcomes at a referral academic centre. Patients and Methods: A RAKT programme was developed in 2016 at our institution following structured modular training. Specific inclusion/exclusion criteria for both living and deceased donors were set. Data from patients undergoing RAKT from January 2017 to April 2018 were prospectively collected in an a priori developed web‐based data set. RAKT followed the principles of the Vattikuti Urology Institute–Medanta technique, with specific technical modifications based on clinical recipient characteristics, as well as surgeon's skills and preference during the learning curve. Technical feasibility of RAKT from deceased donors and evaluation of perioperative and early functional outcomes were the main study endpoints. Results: In all, 17 RAKTs were performed during the study period. Of these, six were from living donors and 11 were from deceased donors. All RAKTs were successfully completed without need of conversion. The median (interquartile range [IQR]) console time was 190 (160–220) min and the median (IQR) estimated blood loss was 120 (110–140) mL. The median times to complete venous, arterial and uretero–vesical anastomoses were 21, 22 and 21 min, respectively. The median (IQR) length of stay was 8 (6–12) days. At a median (IQR) follow‐up of 8 (6–11) months, five (30%) complications were recorded. Of these, four (24%) were minor (Clavien–Dindo Grade I–II) and one major (Clavien–Dindo Grade IIIb, requiring graft nephrectomy). Overall, two patients were still on dialysis at last follow‐up. A significant improvement in graft function was recorded progressively at all postoperative time points. Conclusion: Our preliminary experience outlines that: (i) the development of a RAKT programme is feasible in centres experienced in robotic surgery and open kidney transplantation; (ii) RAKT from deceased donors is feasible from both a technical and logistical perspective; and (iii) RAKT from deceased donors appears to achieve favourable early postoperative and functional outcomes. Larger studies with longer follow‐up are needed to confirm these findings and compare the outcomes of RAKT from deceased donors with those from living donors.